2008
DOI: 10.1016/j.molcel.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Dominant and Redundant Functions of TFIID Involved in the Regulation of Hepatic Genes

Abstract: To study the in vivo role of TFIID in the transcriptional regulation of hepatic genes, we generated mice with liver-specific disruption of the TAF10 gene. Inactivation of TAF10 in hepatocytes resulted in the dissociation of TFIID into individual components. This correlated with the downregulation of most hepatocyte-specific genes during embryonic life and a defect in liver organogenesis. Unexpectedly, however, the transcription of less than 5% of active genes was affected by TAF10 inactivation and TFIID disass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
82
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 40 publications
(56 reference statements)
8
82
0
1
Order By: Relevance
“…Likewise, liver-specific disruption of Taf10 gene in Taf10 −/− animals leads to severe growth failure during the second week after birth, more than 50% reduction in body weight at day P30, and premature death at ∼P35 (Fig. 1C) (16). Oil Red O and PAS staining in Ercc1 −/− and Taf10 −/− livers revealed a uniform accumulation of triglycerides and glycogen resulting in a "fatty liver" appearance with unusually large glycogen depots ( Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, liver-specific disruption of Taf10 gene in Taf10 −/− animals leads to severe growth failure during the second week after birth, more than 50% reduction in body weight at day P30, and premature death at ∼P35 (Fig. 1C) (16). Oil Red O and PAS staining in Ercc1 −/− and Taf10 −/− livers revealed a uniform accumulation of triglycerides and glycogen resulting in a "fatty liver" appearance with unusually large glycogen depots ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…To assess the contribution of NER in transcription during development, we compared the liver phenotypes of NER-deficient Ercc1 −/− animals that closely mimic a severe form of CS (11) with transcription factor II D (TFIID)-defective Taf10 −/− mice exhibiting a liver-specific defect in transcription initiation (Taf10 −/− -Alb-Cre) (16). Ercc1 −/− mice show attenuated growth, resulting in cachectic dwarfism during the second week of life and premature death before postnatal day P35 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It therefore seems possible that an as yet unidentified liver-specific core promoter recognition complex partially replaces canonical TFIID during or following differentiation. Although it has been suggested that fetal or postnatal induction of transcription by TFIID would be sufficient to establish a gene's expression throughout the organism's life, and that future rounds of transcription may be core promoter recognition complex independent, such a model has the clear disadvantage of excluding alterations in expression following physiological or environmental change (11). Future identification of a hepatocyte-specific complex or complexes would provide a more parsimonious mechanism of transcriptional change during liver development, regeneration, and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In myotubes, an alternative core component, TAF3, is retained and required for myogenic differentiation. An additional recent example of the relative dispensability of TFIID was the finding that inactivation of TAF10 has little or no affect on adult hepatic gene expression (11). Thus, the notion of switching or "remodeling" of the core promoter machinery may be more widespread than initially appreciated.…”
mentioning
confidence: 99%
“…Notably, it has been shown that individual TAFs are required for the expression of only a specific subset of genes (35)(36)(37)(38), and that the TFIID, or any of its other forms, was recruited in core promoters by a direct interaction between TAFs and their genespecific activators (39). Given that TAF4b target promoter selectivity is enhanced by activators such as c-Jun and Sp-1 (12), we propose a synergistic function of the two factors, c-Jun and TAF4b, through their interaction in which TAF4b is the coactivator of AP-1 during regulation of AP-1 target genes (Fig.…”
Section: Discussionmentioning
confidence: 99%